Cover Feature: Tuning of Oxidation Potential of Ferrocene for Ratiometric Redox Labeling and Coding of Nucleotides and DNA (Chem. Eur. J. 6/2020). Issue 6 (16th December 2019) - Simonova, Anna; Magriñá, Ivan; Sýkorová, Veronika; Pohl, Radek; Ortiz, Mayreli; Havran, Luděk; Fojta, Miroslav; O'Sullivan, Ciara K.; Hocek, Michal
Abstract : Substituted ferrocene derivatives with tuned redox potentials were tested as redox labels for electrochemical detection and coding of nucleobases in DNA. The ferrocene‐linked nucleotides were enzymatically incorporated to DNA and analyzed by using capture probes on gold electrodes. Ferrocenecarboxamide and ethynylferrocene were used as tags for orthogonal ratiometric coding and analysis of cytosine and adenine in DNA. More information can be found in the Full Paper by M. Fojta, C. K. O′Sullivan, M. Hocek, et al. on page 1286 .